PERENCANAAN BENDUNG PROGOPISTAN DI KABUPATEN TEMANGGUNG, JAWA TENGAH - Herdi Janitra; Irzal Lathanza; Suharyanto Suharyanto; Hary Budieny (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2014)
Progopistan Weir is fix weir for irrigation necessary, it had built on Progo River, with area flow of river is 70,116 km2, it is location on Gemawang District, Temanggung Residency in Central Java special territory. Progo River watershed in the region especially those in Gemawang District, Kandangan district, Kaloran District, Kedu District, Temanggung Residency in Central Java there is still rain-fed agriculture. In its development, the availability of irrigation water to irrigate the area is considered very less, so that people suggested that services can be improved through the development of irrigation dam which can reach all areas. Before the dam was first planned analysis so unknown flood discharge for the return period of 50 years was 234.64 m3, and Debit retrieval of 2.42 m3/second. Progopistan weir will design with specific, such as ogee summit 6,3 m tall, USBR type III for Stilling Basin and also completed with sand trap. Canal for slice, gate for intake and slice and Retaining walls. Progopistan weir spend of fund around Rp. 6,9 billion and time schedule for construction around 196 working days.